Non-proteinaceous salivary compounds of a predatory bug cause histopathological and cytotoxic effects in prey. (15th July 2022) - Campos, Juliana Mendonça; Martínez, Luis Carlos; Plata-Rueda, Angelica; Carneiro, Lenise Silva; Weigand, Wolfgang; Wilcken, Carlos Frederico; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: N, N -dimethylaniline and 1, 2, 5 -trithiepane, present in the salivary glands of Podisus nigrispinus Dallas (Heteroptera: Pentatomidae), are toxic compounds which kill prey. The insecticidal activity and midgut cytotoxicity in Spodoptera frugiperda (J. E. Smith (Lepidoptera: Noctuidae) caterpillars fed on a diet with lethal concentrations of N, N -dimethylaniline and 1, 2, 5 -trithiepane were evaluated. Midgut cell damage was evaluated with both light and transmission electron microscopy. The LC50 and LC90 of N, N -dimethylaniline were 0.611 and 0.818 μg L −1, respectively, and for 1, 2, 5 -trithiepane they were 0.671 and 0.885 μg L −1, respectively. Vacuolization in the digestive and goblet cells occurred after 1 h of exposure in the midgut of the insects treated with either N, N -dimethylaniline and 1, 2, 5 -trithiepane. Changes caused by N, N -dimethylaniline and 1, 2, 5 -trithiepane in the midgut of S. frugiperda caterpillars may affect digestion and nutrient absorption with negative impacts on the insect's development and survival. The non-proteinaceous N, N -dimethylaniline and 1, 2, 5 -trithiepane compounds have insecticidal effects, confirming the potential use on S. frugiperda caterpillars through oral administration. Graphical abstract: Image 1 Highlights: The N, N -dimethylaniline and 1, 2, 5 -trithiepane are produced by predatory bug and responsible to cause prey death. Chemical compounds promote histopathological and cytotoxic changes in midgut prey via ingestion. N, N -dimethylaniline and 1, 2, 5 -trithiepane have potential use for the control of insect pests.